KARAKTERISTIK KLINIKOPATOLOGI KARSINOMA SERVIKS DI RUMAH SAKIT DR. M. DJAMIL PADANG PERIODE 2018 – 2021 - Fedrivia, Rannia; Asri, Aswiyanti; Elfi, Eka Fithra; Muhammad, Syamel; Mulyani, Henny; Nofita, Eka (SINERGI : Jurnal Riset Ilmiah, 2025)
Cervical carcinoma is a malignant tumor of cervical epithelial cells which is more than 90% caused by the human papillomavirus. Clinicopathology factors in cervical carcinoma such as age, history of parity, history of sexual intercourse, history of clinical manifestations, histopathology type and degree of differentiation are known to affect the prognosis. This study aims to determine the clinicopathological characteristics of cervical carcinoma at Dr. M. Djamil Hospital Padang in 2018-2021. This research is a descriptive research with the number of samples, 108 patients with confirmed cervical carcinoma. Research was conducted from March 2022 to March 2023 at the Laboratory of Anatomical Pathology, Dr. M. Djamil Padang. The results found that majority of cervical carcinoma patients is ≥45 years old (74,1%) with all patients are married (100%). The clinical manifestation that most patients complained about was vaginal bleeding 99.1% and 91,7% patients of cervical carcinoma were multiparity. The most common histopathological type of cervical carcinoma is squamous cell carcinoma (77.8%) and the highest degree of differentiation is moderate (47.2%). The cervical carcinoma patients at the Laboratory of Anatomical Pathology Dr. M. Djamil Hospital in 2018-2021 were found in the early elderly age group and are in advanced stage so it is necessary to carry out early detection and prevention of cervical carcinoma.